2013
DOI: 10.1039/c2cc38389f
|View full text |Cite
|
Sign up to set email alerts
|

Linking gold nanoparticles with conductive 1,4-phenylene diisocyanide–gold oligomers

Abstract: A major challenge to fabricating molecular electronic circuits 1 is the difficulty of simultaneously chemically bonding molecular components to two metal electrodes. This can be accomplished by adjusting the electrode separation to match the molecular dimensions using break junctions 2-5 or by using a sharp tip to vary the electrode-surface spacing. 6 Such approaches provide detailed information on molecular conduction, but are not easily extended to planar systems required for a realistic circuit. 7Molecularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 36 publications
(47 reference statements)
3
57
1
Order By: Relevance
“…Similar behavior has been found for PDI-linked gold nanoparticles and provides corroborative evidence that 1,4-BDT forms similar oligomeric linkages. 95 It has been shown previously that this behavior can be adequately reproduced by a model due to Abeles for thermally assisted tunneling through an array of nanoparticles. 108 This model predicts that the sheet resistance R is given by R = R 0 exp(+2(C/kT) 1/2 ), where C = χsE c 0 , s is the average spacing between particles, χ = (2mϕ/ℏ 2 ) 1/2 , ϕ is the height of the tunneling barrier, m is the electron mass, E c 0 is the Coulomb charging energy, and R 0 is a constant.…”
Section: ■ Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Similar behavior has been found for PDI-linked gold nanoparticles and provides corroborative evidence that 1,4-BDT forms similar oligomeric linkages. 95 It has been shown previously that this behavior can be adequately reproduced by a model due to Abeles for thermally assisted tunneling through an array of nanoparticles. 108 This model predicts that the sheet resistance R is given by R = R 0 exp(+2(C/kT) 1/2 ), where C = χsE c 0 , s is the average spacing between particles, χ = (2mϕ/ℏ 2 ) 1/2 , ϕ is the height of the tunneling barrier, m is the electron mass, E c 0 is the Coulomb charging energy, and R 0 is a constant.…”
Section: ■ Resultsmentioning
confidence: 81%
“…109 The prediction that the resistance should vary with temperature as ln(R) = (α/√T) + β is in agreement with the results shown in Figure 7, as well as for PDI-linked gold nanoparticles. 95 The Abeles model predicts that the value of α in the above equation should depend on ln(initial film resistance) and such a plot is displayed in Figure 8, which yields a good straight line with a slope of 4.2 ± 0.2, which is slightly larger than for the corresponding plot for PDI-linked nanoparticles, which gave a slope of 3.7 ± 0.2. 95 ■ DISCUSSION 1,4-BDT adsorbs molecularly at low temperatures on Au (111) and reacts to form an η 1 -bonded thiolate on heating to ∼166 K ( Figure 1).…”
Section: ■ Resultsmentioning
confidence: 97%
“…In contrast, obvious aggregation of Au NIs is found for the bare or non-functionalized Au NI template (Fig. 42,43 The complementary case has also been examined by preparing Au on Fe NrPs by magnetron sputtering (Fig. This is believed to be due to eld-induced relocation of Au nanoparticles smaller than 10 nm.…”
Section: Resultsmentioning
confidence: 99%
“…34 It has been demonstrated that near-IR absorption of Au-Fe 3 O 4 can be utilized for potential applications as a photothermal treatment of cancer and a drug delivery system. [42][43][44][45][46] PDI is found to have the tendency to self-assemble with gold to form -(Au-PDI) noligomers. 38,39 Various methods of synthesizing Fe oxides have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The molecule bridged the gold islands and increased conductivity from 6.5 × 10 −10 to 270 × 10 −10 S after 2000 s of exposure. The authors showed that the presence of two isocyanide groups in the PDI molecule is essential to achieve conductivity: Exposure to phenyl isocyanide hardly improved the conductivity [ 119 ].…”
Section: Reviewmentioning
confidence: 99%